LncRNA260-specific siRNA targeting IL28RA gene inhibit cardiomyocytes hypoxic/reoxygenation injury - Gong, Ge; Yang, Xin-Xing; Li, Yanyan; Geng, Hong-Yu; Yang, Zhi-Jian; Wang, Lian-Sheng; Kim, Hyun Jun; Lu, Xin-Zheng (Journal of Thoracic Disease; Vol 9, No 8 (August 28, 2017): Journal of Thoracic Disease, 2017)
Background: The interleukin 28 receptor alpha (IL28RA) gene was indicated to be associated with apoptosis. However, it was not clear whether long non-coding RNA 260 (lncRNA 260)-specific siRNA targeting IL28RA gene could inhibit hypoxic reoxygenation (H/R) cardiomyocytes injury or not. To explore the mechanisms underlying the protective effects of lncRNA260-specific siRNA-mediated inhibition of IL28RA from H/R injury in car-diomyocytes, the current research was performed. Methods: The primary neonatal rat cardiomyocytes were transfected with three different pairs of siRNA specific to lncRNA260 targeting IL28RA gene and then were undergone with the conditions simulating H/R injury. Results: All three groups of cardiomyocytes treated with lncRNA260-specific siRNA experienced significantly decreased levels of lactate dehy-drogenase activity and apoptosis rate relative to the non-treatment and negative control groups (P